ENHANCE HUMAN RESOURCE MANAGEMENT FOR THE QUALITY OF HIGHER EDUCATION - Hendra Utama (Jurnal Scientia, 2023)
The purpose of analyzing the human resources of universities is to understand the profile of human resources of universities, the quality of human resources of universities, and determine the quality of universities by using data in 2009/2010. The methods used in this analysis were documentation studies and surveys. In addition, key performance indicators (KPIs) from the 2010-2014 Education Strategy Plan were used to assess the quality of HEIs. The results showed that although private HEIs accounted for 97.24% of existing HEIs, their students only accounted for 58.39% and their lecturers for 71.83%. Human resource management is very important in improving the quality of education. With the support of quality resources, universities can progress and develop. Improving the quality of education is determined by the leadership of educational institutions in managing their human resources. In managing human resources, university leaders are key in improving the quality of education. College leaders are required to always develop human resources in order to create quality education: Education, Quality, Human Resources